2019
DOI: 10.1111/mcn.12814
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iron intake during pregnancy and the risk of small for gestational age

Abstract: Studies of iron and its association with the risk of small for gestational age (SGA) show inconsistent results. Consuming iron supplements during pregnancy is controversial because of possible risks. This study assessed the association between iron intake and the risk of having an SGA newborn and whether iron intake is associated with gestational diabetes. A case-control study of 518 pairs of Spanish women who were pregnant and attending five hospitals was conducted. Groups were matched 1:1 for age (±2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Martínez‐Galiano et al 25 suggest that iron is fundamental for placental growth and embryonic organogenesis within the first 12 weeks, but any excess of iron after the end of this period may result in the disruption of glucose metabolism. This study showed no link between iron supplementation and the development of GDM in patients with anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Martínez‐Galiano et al 25 suggest that iron is fundamental for placental growth and embryonic organogenesis within the first 12 weeks, but any excess of iron after the end of this period may result in the disruption of glucose metabolism. This study showed no link between iron supplementation and the development of GDM in patients with anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…The only protective factor for the occurrence of FGR during the third trimester in our study was iron supplementation. Iron is an important micronutrient in pregnancy because of its role in the growth, haematopoiesis, and development of the fetus [28]. Previous studies have also confirmed that iron supplements have a protective effect against SGA, even in women without anemia [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Iron is an important micronutrient in pregnancy because of its role in the growth, haematopoiesis, and development of the fetus [28]. Previous studies have also confirmed that iron supplements have a protective effect against SGA, even in women without anemia [28,29]. However, there are also studies that didn't find any association between iron supplementation and SGA [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Nut consumption during early pregnancy is associated with long-term childhood neuropsychological development. A maternal diet with significant consumption of pastries during pregnancy, consisting mainly of baked and sugary products, combined with a longer period of breastfeeding, can lead to the development of food allergies, suggesting a harmful effect of trans fat in the baby [58][59][60][61][62][63][64][65][66][67][68]. The maternal diet can even cushion the risk of other risk factors for neonatal pathology [63].…”
Section: Effects Of Nutritional Status Of Pregnant Women On the Fetusmentioning
confidence: 99%
“…The systematic intake of micronutrient, iron, and multivitamin supplements in all pregnant women is not recommended as it has not been found to be exempt of risks. This advice must be adapted to the real needs of each woman [65,76,77]. However, folic acid supplementation by all pregnant women from the preconception stage for preventing neural tube defects does have support, although it has also been associated with adverse effects during pregnancy [78,79].…”
Section: Nutritional Recommendations For Pregnant Women By Health Promentioning
confidence: 99%